From work to community: how social participation and retirement can benefit older adults’ depression - Zhan, Yiyu; Ning, He; Zhang, Yuchen (Frontiers in Psychiatry, 2025)
ObjectivesThe retirement phase and social participation influence the depressive symptoms of older individuals. Nonetheless, the fundamental mechanisms connecting these factors remain unclear. This analysis examined mediating social participation in the relationship between older adults’ retirement and depressive symptoms.MethodsThe study analyzed 9,103 Chinese individuals aged 60 and above utilizing the 2020 China Health and Retirement Longitudinal Study (CHARLS). Researchers evaluated participants’ depression utilizing the Center for Studies in Epidemiology Depression Scale (CESD-10). The hierarchical multiple regression models were utilized to evaluate the link between retirement and depression, through cross-sectional analyses, along with the possible influence of social participation on this relationship.ResultsRetirement significantly reduce older individuals’ depression and improves their mental health state. In addition, social participation as a mediating variable further enhanced the beneficial impacts of retirement on the mental health state.ConclusionThis research discovered that retirement indirectly influences older adults’ depression, with social participation playing a significant impact. Thus, it establishes a foundation for mitigating psychological issues in this demographic. Engaging in or sustaining social activities during later life enhances the mental well-being of older individuals. Promoting social participation among older individuals is a viable approach to reduce depression and facilitating successful aging initiatives in this demographic.